Pancasila Student Profile Strengthening Project: Boosting The Environmental Awareness in Primary School - Dewi, Sari; Surjanti, Jun; Nasution, Nasution; Amin, Saiful; Kurniawan, Muchammad Akbar (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
The Strengthening the Profile of Pancasila Students (Projek Penguatan Profil Pelajar Pancasila/P5) project is an effective synergy to raise awareness about waste management. This involves integrating learning materials on the negative impacts of waste into the school curriculum, as well as providing the means to implement waste reduction and management practices in the school environment and beyond. This study aims to determine the implementation of P5 in the utilisation of plastic waste as an effort to strengthen the environmental awareness character. Observation, documentation, and interviews were used to collect data.  The data that had been collected was analysed using interactive techniques. The results showed that the implementation of P5 was carried out through 4 stages, namely 1) introduction, 2) contextualisation, 3) action, and 4) reflection and follow-up. The implementation of this project goes well in strengthening the character of students to be aware of the environment, as evidenced by the production of plastic processing products, such as tablecloths, flower vases, pencil cases, chairs and tables. Further studies should consider exploring strategies to enhance community engagement and active participation within the school. Future research could also investigate the role of partnerships with external stakeholders, such as NGOs, local businesses, or environmental experts, to provide additional resources and expertise.